Nuevos Modelos Locales de Relaciones Laborales en Italia. Una Primera Reflexión. - Francesca Malzani (TRABAJO. Revista Iberoamericana de Relaciones Laborales, 2017)
The aim of this paper is to identify some trends of collective bargaining in Italy, in a context of industrial relations profoundly changed in recent years. In particular, moving from the changed landscape of industrial relations, the paper focuses on the adoption of instruments of welfare and conciliation in the second level agreements in our area. The choice of these two issues is not accidental: it falls under the aspects that, joined with others of course (eg. training, participation, etc.), contribute to the creation of holistic models of quality of work